USING FAIRY TALES IN TEACHING ENGLISH TO YOUNG LEARNERS - D.B.Kayumov,; Baqoyeva Bibihonim, (TADQIQOTLAR, 2026)
Abstract This article explores the effectiveness of using fairy tales as a pedagogical tool in teaching English to young learners. It discusses how fairy tales can enhance language acquisition,  stimulate  imagination,  and  promote  cultural  understanding  among children. The narrative structure, rich vocabulary, and moral lessons embedded in fairy tales make them an engaging resource for educators. The article also highlights various activities and strategies that teachers can implement to incorporate fairy tales into their English language curriculum, thus fostering a love for reading and learning in young students.